A clinical herbal prescription Gu-Shu-Kang capsule exerted beneficial effects on the musculoskeletal system of dexamethasone-treated mice by acting on tissue IGF-1 signalling pathway. (31st December 2022) - Li, Xiao-Li; Wang, Liang; He, Ming-Chao; Li, Wen-Xiong; Zhang, Jia-Li; Fu, Yong-Fang; Zhang, Yan
Abstract: Context: Gu-Shu-Kang (GSK) is a clinical traditional Chinese medicine prescription for the treatment of primary osteoporosis. Objective: This study investigates the protection of GSK against dexamethasone (Dex)-induced disturbance of musculoskeletal system in male mice and to identify the underlying mechanism. Materials and methods: Male C57BL/6 mice in Dex-treated groups were orally administered (i.g.) with vehicle, low dose (0.38 g/kg), middle dose (0.76 g/kg), or high dose (1.52 g/kg) of GSK for 8 weeks. A control group was designed without any treatment. The quadriceps femoris, tibialis anterior and gastrocnemius were harvested. Molecular expression was determined by RT-PCR and immunoblotting. Results: Treatment with GSK enhanced weight-loaded swimming time (from 411.7 ± 58.4 s in Dex group to 771.4 ± 87.3 s in GSK-M) and grip strength (from 357.8 ± 23.9 g in Dex group to 880.3 ± 47.6 g in GSK-M). GSK produced a rise in cross-sectional area of myofibers and promoted a switching of glycolytic-to-oxidative myofiber. The administration with GSK affected expression of muscle regulatory factors shown by the down-regulation in MuRF-1 and atrogin-1 and the up-regulation in myogenic differentiation factor (MyoD) and myosin heavy chain (MHC). GSK stimulated tissue IGF-1 signalling pathway (IGF-1R/PI3K/Akt), not only in skeletal muscle but also in bone associated with the amelioration of trabecular bone mineral density and the improvement of osteogenesis. Conclusions: These findings revealed the potential mechanisms involved in the beneficial effects of Gu-Shu-Kang on musculoskeletal system in mice with challenging to dexamethasone, and this prescription may have applications in management for muscle atrophy and osteoporosis triggered by glucocorticoid.